Program Pendidikan Kesehatan Tentang Gizi pada Balita di Desa Duman Kecamatan Lingsar Kabupaten Lombok Barat - Fatmawati, Nurul; Zulfiana, Yesvi; Handayani, Sri (LPPM Universitas Bumigora, 2023)
Indonesia is experiencing 2 major nutritional problems. Apart from being malnourished, we are also starting to be overnourished. Deficiency and excess nutrition both have a negative impact. Malnutrition is closely related to slow body growth (especially in children), low immune system, lack of intelligence and low productivity. PSG results data in 2017, the prevalence of stunting in the Province of NTB was 37.2% higher than the national average of 29.6%. This figure also increases when compared to the year. 2016, namely 29.9% or an increase of 7.29%. For the highest stunting prevalence in Sumbawa Regency, which is 41.9%, followed by Central Lombok 39.9%, Dompu 38.3%, Mataram City 37.8%, North Lombok 37.6%, Bima 36.6%, Bima City 36 .3%, West Lombok 36.1% and East Lombok 35.1%. The method of implementing this service consists of tree stages. The first is the planning of activities to be carried out and the second stage is the implementation of community service activities. The implementation of community service activities in the form of health counseling about Nutrition in Toddlers has a positive impact in the form of increasing the mother's knowledge of Nutrition in Toddlers.